Demographic, behavioral, dietary, and socioeconomic characteristics related to persistent organic pollutants and mercury levels in pregnant women in Japan. (August 2015) - Miyashita, Chihiro; Sasaki, Seiko; Saijo, Yasuaki; Okada, Emiko; Kobayashi, Sumitaka; Baba, Toshiaki; Kajiwara, Jumboku; Todaka, Takashi; Iwasaki, Yusuke; Nakazawa, Hiroyuki; Hachiya, Noriyuki; Yasutake, Akira; et al.
Highlights: PCDDs/PCDFs and DL-PCBs, and PFOS decreased with maternal smoking history. NDL-PCBs and, PCDDs/PCDFs and DL-PCBs increased with maternal alcohol consumption during pregnancy. Total hair Hg increased with household income. Beef and fish/seafood intake may be important exposure sources of NDL-PCBs. Chemical exposure and elimination rate may be related to lifestyle factors. Abstract: Persistent organic pollutants and mercury are known environmental chemicals that have been found to be ubiquitous in not only the environment but also in humans, including women of reproductive age. The purpose of this study was to evaluate the association between personal lifestyle characteristics and environmental chemical levels during the perinatal period in the general Japanese population. This study targeted 322 pregnant women enrolled in the Hokkaido Study on Environment and Children's Health. Each participant completed a self-administered questionnaire and a food-frequency questionnaire to obtain relevant information on parental demographic, behavioral, dietary, and socioeconomic characteristics. In total, 58 non-dioxin-like polychlorinated biphenyls, 17 dibenzo-p-dioxins and -dibenzofuran, and 12 dioxin-like polychlorinated biphenyls congeners, perfluorooctane sulfonate, perfluorooctanoic acid, and mercury were measured in maternal samples taken during the perinatal period. Linear regression models were constructed against potential related factors for each chemical concentration. Most concentrations of environmental chemicals were correlated with the presence of other environmental chemicals, especially in the case of non-dioxin-like polychlorinated biphenyls and, polychlorinated dibenzo-p-dioxins and -dibezofurans and dioxin-like polychlorinated biphenyls which had similar exposure sources and persistence in the body. Maternal smoking and alcohol habits, fish and beef intake and household income were significantly associated with concentrations of environmental chemicals. These results suggest that different lifestyle patterns relate to varying exposure to environmental chemicals.